Kidney involvement in malaria: an update - Silva Junior, Geraldo Bezerra da (2017)
Malaria is an infectious disease of great importance for Public Health, as it is the most prevalent endemic disease in the world, affecting millions of people living in tropical areas of the globe. Kidney involvement is relatively frequent in infections by P. falciparum and P. malariae, but has also been described in the infection by P. vivax. Kidney complications in malaria mainly occur due to hemodynamic dysfunction and immune response. Liver complications leading to hepatomegaly, jaundice and hepatic dysfunction can also contribute to the occurrence of acute kidney injury. Histologic studies in malaria also evidence glomerulonephritis, acute tubular necrosis and acute interstitial nephritis. It is also possible to find chronic kidney disease associated with malaria, mainly in those patients suffering from repeated episodes of infection. Plasmodium antigens have already been detected in the glomeruli, suggesting a direct effect of the parasite in the kidney, which can trigger an inflammatory process leading to different types of glomerulonephritis. Clinical manifestations of kidney involvement in malaria include proteinuria, microalbuminuria and urinary casts, reported in 20 to 50% of cases. Nephrotic syndrome has also been described in the infection by P. falciparum, but it is rare. This paper highlights the main aspects of kidney involvement in malaria and important findings of the most recent research addressing this issue.